ECONOMIC ANALYSIS OF STRUCTUTAL CHARACTERISTICS OF POULTRY EGG MARKETING IN KANO METROPOLIS, KANO STATE, NIGERIA - Lawal, A. T.; Yusuf, A. O.; Dambazau, S. A.; Ahmad, Y. S.; Adomi, A. A.; Sadiq, M. S.; Suleiman, I.; Suleiman, I.; Barau, S. S. (FUDMA JOURNAL OF SCIENCES, 2020)
This study analyzed the structural characteristics of poultry egg marketing in five selected markets in Kano metropolis. Data were collected with the aid of questionnaires and were analyzed using descriptive statistics and gini coefficient. The study revealed that all marketers were males with an average age of 38 years and 27 years for wholesalers and retailers respectively. For wholesalers, the average household size is 8 and 5 for the retailers. According to the result, the wholesalers had 15 years as mean years of experience in poultry-egg marketing and retailers have 7 years. The result showed that the average duration of stay of the wholesalers is 15 years and 7 years for retailers. The study showed that 79.5% of the wholesalers were married and 20.5% are single while for the retailers 65.9% are married and 34.04% are single. The result indicated that about 66.7% of the wholesalers and 87.2% are literates. Result of the Gini coefficient analysis showed a high level concentration of 0.48 and 0.54 for wholesalers and retailers. The result shows that 100% of both wholesalers and retailers have free entry and exit in to the egg market, majority of the wholesalers (79.5%) do not belong to any cooperative society, while the remaining (20.5%) belong to one or more cooperative societies while 100% of the retailers do not belong to any cooperative group. It is recommended that good roads and storage facilities should be provided for the people in order to reduce the rate .
Keywords: Analysis, Structural Characteristics, Poultry Egg, Marketing and Kano Metropolis